Delivery systems for biopharmaceuticals. Part I: nanoparticles and microparticles - Silva, Ana Catarina (2020)
Pharmaceutical biotechnology has been showing therapeutic success never achieved with conventional drug molecules. Therefore, biopharmaceutical products are currently well-established in clinic and the development of new ones is expected. These products comprise mainly therapeutic proteins, although nucleic acids and cells are also included. However, according to their sensitive molecular structures, the efficient delivery of biopharmaceuticals is challenging. Several delivery systems (e.g. microparticles and nanoparticles) composed of different materials (e.g. polymers and lipids) have been explored and demonstrated excellent outcomes, such as: high cellular transfection efficiency for nucleic acids, cell targeting, increased proteins and peptides bioavailability, improved immune response in vaccination, and viability maintenance of microencapsulated cells. Nonetheless, important issues need to be addressed before they reach clinics. For example, more in vivo studies in animals, accessing the toxicity potential and predicting in vivo failure of these delivery systems are required. This is the Part I of two review articles, which presents the state of the art of delivery systems for biopharmaceuticals. Part I deals with polymeric and lipid microparticles and nanoparticles.